Combination of DXA and BIS Predicts Jump Power Better Than Traditional Measures of Sarcopenia. (2nd July 2021) - Rush, Benjamin; Binkley, Neil; Krueger, Diane; Yamada, Yosuke; Kuchnia, Adam J
ABSTRACT: Traditional diagnostic criteria for sarcopenia use dual‐energy X‐ray absorptiometry (DXA)‐measured appendicular lean mass (ALM), normalized to height (ALM/ht 2 ) or body mass index (ALM/BMI) to define low muscle mass. However, muscle function declines with aging before the loss of muscle mass is detected by ALM. This is likely due, in part, to qualitative muscle changes such as extracellular and intracellular fluid compartment shifts uncaptured by DXA. We propose combining bioimpedance spectroscopy (BIS), which estimates extracellular and intracellular compartment volume, with DXA to more accurately predict muscle function. This combination may help incorporate muscle quality, thereby improving sarcopenia diagnosis. We cross‐sectionally analyzed data from 248 Black and White participants aged 25 to 75 years from the Midlife in the United States Refresher Cohort. We proposed two novel muscle measures: ALM corrected by the BIS‐derived whole‐body extracellular to intracellular fluid ratio (E/I) and leg lean mass (LLM) corrected by leg‐specific E/I, creating (ALM/(E/I)W ) and (LLM/(E/I)L ), respectively. We compared the associations of traditional muscle measures, ALM/(E/I)W, and LLM/(E/I)L, with grip strength and lower limb power using jumping mechanography. LLM/(E/I)L explained jump power best at R 2  = 0.803 compared with ALM/(E/I)W ( p  < 0.0001) and all other measures. ALM/(E/I)W explained jump power second best ( R 2  = 0.759) but not significantly better than traditional muscle measures. No muscle measure performed better than covariates when predicting handgrip strength. LLM/(E/I)L outperformed ALM/ht 2 and ALM/BMI when predicting jump power. We propose LLM/(E/I)L is a powerful and clinically relevant method that accounts for muscle quality. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : We show that the combination of DXA and BIS derived leg lean mass corrected by the ratio of extracellular fluid in intracellular fluid better predicts jump power than appendicular lean mass adjusted by height or body mass index. Appendicular lean mass or leg lean mass corrected by height, body mass index, or the ratio of intracellular fluid to extracellular fluid did not predict handgrip strength better than covariates only.